THE HUANCA AND ITS SYMBOLIC DIMENSION IN ARCHAEOLOGY OF CENTRAL SIERRA - Farfán Lobatón, Carlos (2012)
Archaeology has always explained the nature of the material culture left by ancient inhabitants of a settlement. As it explained human behavior and inferred some meanings of cultural, social and economic. But archeology by nature of their data and at times by methodological and epistemological problems falls into extreme positivist or functionalist. To avoid these extremes, try to give an approach based on the interpretation of symbolic meanings, based on archaeological data as empirical and ethnographic and ethno historic data and testable data to explain the behavior of society’s last. In this case, we refer to an icon called Polymorphic Huanca, who is usually a long lump of stone and is set to stand or planted in the ground. Their meanings and nature still exist in the Andean communities and can be contrasted with the ethno historical data and oral tradition, as archaeologically is a sample question that existed in the context of archaeological populations and crop areas, preserving their traditions and customs until now. Therefore, the registration and the characterization will allow us to contextualize the archaeological sites.